(untitled) (KYAMC Journal, 2017)
Background: The field of Physical Medicine and Rehabilitation focuses on the restoration of health and function and reintegration of the patient into the community, Providing services (outdoor & indoor patients) of physical medicine & rehabilitation (PMR) department was started in 2015. Since establishment, department of Physical Medicine is providing services as outdoor basis regularly. Aim & Objectives: The purpose of the study was to observe the disease pattern and demographic characteristics of patients attending the department of Physical Medicine and Rehabilitation in a tertiary care hospital. Methods: This is a retrospective study carried out at the department of Physical Medicine and Rehabilitation in Khwaja Yunus Ali Medical College Hospital (KYAMCH), Sirajganj for the period of one year from 1st January, 2016 to 31st December, 2016. Results: Total eighteen hundred sixty five (n = 1865) patients were studied, of which 46.21% were male and 53.78% were female. The mean age was 34.64 ± 5.36 years; maximum patients (25.14%) belong to 31-40 years of age. Maximum patients (78%) were come from out of Sirajgonj District specially North Bengal. Regarding disease pattern, 21.60% were PLID, 10.99% stroke, cervical spondylosis 11.15%, lumbar spondylosis 11.52%, frozen shoulder 10.83%, low back pain 9.49%, osteoarthritis 8.25%, facial palsy 0.43% rheumatoid arthritis 5.47%, seronegetavive Spondyloarthopathy 0.26%, GBS 0.10% acute neck sprain/strain 5.68% and others 4.18%. Conclusion: A large scale multi-centered study should be performed in the country. A uniform data system should be constructed for Medical rehabilitation in Bangladesh. Maximum patients were having PLID, Cervical spondylosis, lumbar spondylosis, Stroke & Frozen shoulder. KYAMC Journal Vol. 8, No.-1, Jul 2017, Page 33-37